LightGuide: Projected Visualizations for Hand Movement Guidance - Sodhi, Rajinder; Benko, Hrvoje; Wilson, Andy (CHI '12 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2012)
LightGuide is a system that explores a new approach to gesture guidance where we project guidance hints directly on a user’s body. These projected hints guide the user in completing the desired motion with their body part which is particularly useful for performing movements that require accuracy and proper technique, such as during exercise or physical therapy. Our proof-of-concept implementation consists of a single low-cost depth camera and projector and we present four novel interaction techniques that are focused on guiding a user’s hand in mid-air. Our visualizations are designed to incorporate both feedback and feedforward cues to help guide users through a range of movements. We quantify the performance of LightGuide in a user study comparing each of our on-body visualizations to hand animation videos on a computer display in both time and accuracy. Exceeding our expectations, participants performed movements with an average error of 21.6mm, nearly 85% more accurately than when guided by video.